Russia Sovereignty and Regional Security: The Asymmetric Conflict of the Russian Federation Military in Ukraine (2014) - Hendra Manurung (Verity: Jurnal Ilmiah Hubungan Internasional (International Relations Journal), 2017)
The Russia Federation is global actor in applying strict policies against the Ukraine. In pursuing the state’s political goals from Moscow, the escalation of military operations in 2014 defined the way the state behaves. Through a combination of military and non-military operations, Russia is now slowly regaining its power through the annexation of the Crimea. The effectiveness of this method is used to determine Russia’s contemporary warfare strategy. It thus explains how Russia's foreign policy and defense policy from 2000 to 2013 has dependence on Ukraine's strategic environment on Russia, and Russia's national interest in Ukraine. The main focus of this paper is on the achievement of Russia’s political objectives in its military operation in Ukraine and analysis on Russia’s national security components that significantly influence the interaction of this asymmetric conflict. BAHASA INDONESIA ABSTRAK: Federasi Rusia merupakan aktor global yang menerapkan kebijakan tegas terhadap Ukraina. Guna mencapai tujuan politik nasional Rusia yang dikendalikan dari Moskwa, melalui operasi militer di tahun 2014, didefinisikan bagaimana negara tersebut berperilaku. Melalui kombinasi operasi militer dan non-militer, Rusia secara perlahan memperoleh kekuasaan melalui aneksasi Krimea. Efektivitas metoda ini dipergunakan untuk menentukan strategi perang Rusia saat ini. Dengan demikian menjelaskan bagaimana kebijakan luar negeri dan kebijakan pertahanan Rusia dari tahun 2000 hingga 2013 yang memiliki ketergantungan pada lingkungan strategis Ukraina terhadap Rusia, dan kepentingan nasional Rusia pada Ukraina. Fokus utama penelitian ini adalah pencapaian tujuan politik Rusia dalam operasi militer yang dilaksanakan di Ukraina dan menganalisa komponen keamanan nasional Rusia yang signifikan mempengaruhi interaksi konflik asimetrik.